2008
DOI: 10.1021/nl802044t
|View full text |Cite
|
Sign up to set email alerts
|

Robust Plasmon Waveguides in Strongly Interacting Nanowire Arrays

Abstract: Arrays of parallel metallic nanowires are shown to provide a tunable, robust, and versatile platform for plasmon interconnects, including high-curvature turns with minimum signal loss. The proposed guiding mechanism relies on gap plasmons existing in the region between adjacent nanowires of dimers and multi-wire arrays. We focus on square and circular silver nanowires in silica, for which excellent agreement between both boundary element method and multiple multipolar expansion calculations is obtained. Our wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 30 publications
3
109
0
Order By: Relevance
“…Individual wire modes are recovered at large separations, while mode hybridization is observed when the spacing is reduced. 32 Previous studies have demonstrated that, in an array of nanorods, the SPR of the individual nanorods can be viewed as harmonic oscillators that couple to each other, leading to a resonance shift as well as a changed near-field distribution. 33 In the present work, the mean distances between the wire surfaces facing each other decreases from 470 to 370 nm with the nanowires diameters increasing from 30 to 130 nm at the certain area density of 1 Â 10 8 wires/cm 2 (with the assumption of all nanopores in the templates being filled).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual wire modes are recovered at large separations, while mode hybridization is observed when the spacing is reduced. 32 Previous studies have demonstrated that, in an array of nanorods, the SPR of the individual nanorods can be viewed as harmonic oscillators that couple to each other, leading to a resonance shift as well as a changed near-field distribution. 33 In the present work, the mean distances between the wire surfaces facing each other decreases from 470 to 370 nm with the nanowires diameters increasing from 30 to 130 nm at the certain area density of 1 Â 10 8 wires/cm 2 (with the assumption of all nanopores in the templates being filled).…”
Section: Resultsmentioning
confidence: 99%
“…The observed peak broadening can be ascribed to the polydispersity in the nanowires distance and overlap of the gap mode with the metal. 32 The absorbance properties of gold nanowire arrays with different incident angle a were also investigated [ Fig. 3(b)].…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17] Propagating gap plasmons are well understood from a theoretical point of view. 7 Notice that these plasmons are quite different from the resonances that one obtains associated to the excitation of wire pairs using light incident normal to the wires. In particular, retardation in the response of the system is required to have a realistic description of trapped propagating modes.…”
Section: Introductionmentioning
confidence: 89%
“…1,2 Their potential application for on-chip communication and signal processing has stimulated recent investigations of different geometries for plasmon waveguiding intended to optimize the compromise between propagation distance, degree of confinement, and electric field enhancement. Among these structures, interesting results have been reported for particle chains, 3,4 grooves, 5 and wedges 6 carved in planar surfaces, gaps between metallic nanowires, 7 and metallodielectric structures. 8 In particular, gap plasmons have been shown to be excellent candidates to minimize crosstalk between neighboring waveguides, thus allowing a high degree of spatial integration.…”
Section: Introductionmentioning
confidence: 99%
“…In theoretical models, strong subwavelength field enhancements are observed indicating the relevance of imaging on a spatial scale far below the free-space wavelength of the light. Many Ag and Au nanostructures, which are the common model structures for plasmonic studies, have localized plasmonic resonances at these wavelengths with field concentration at wedges or crescents [20][21][22][23].…”
mentioning
confidence: 99%